Effect of trilaciclib administered before chemotherapy in patients with extensive-stage small-cell lung cancer: A pooled analysis of four randomized studies - Ying Liu; Lin Wu; Dingzhi Huang; Qiming Wang; Chen Yang; Li Zhou; Shuguang Sun; Xiaomei Jiang; Ying Cheng (Cancer Treatment and Research Communications)
Background: Trilaciclib is a transient cyclin-dependent kinase 4/6 (CDK4/6) inhibitor that reduces the incidence of chemotherapy-induced myelosuppression (CIM). In this pooled analysis, we evaluated the multilineage myeloprotection, antitumor efficacy, and safety of trilaciclib treatment in patients with extensive-stage small-cell lung cancer (ES-SCLC). Moreover, myeloprotection effect in 1 L, 2 L/3 L population and effect by risk category were explored. Materials and Methods: Patients with ES-SCLC who received trilaciclib were included. Trilaciclib was administered before chemotherapy in four randomized, double-blind, placebo-controlled studies (NCT02499770, NCT03041311, NCT02514447, and NCT04902885), and data were subsequently extracted. The primary endpoints were the duration of severe neutropenia (DSN) in cycle 1 and/or the incidence of severe neutropenia (SN). Results: The data from 325 patients receiving trilaciclib (n = 164) or placebo (n = 161) were pooled. Trilaciclib demonstrated a clinically and statistically significant reduction in DSN in cycle 1 and in the incidence of SN and febrile neutropenia (FN) in the overall, 1 L, 2 L/3 L populations. The myeloprotection effect was greater in patients with a higher number of FN risk categories. Overall, the median progression-free survival was 5.3 months in the trilaciclib and 4.9 months in the placebo group. The median overall survival was 10.9 months in the trilaciclib and 10.1 months in the placebo group. Trilaciclib showed better capability of reducing CIMs incidence compared with prophylactic G-CSF in the overall and 1 L population. Conclusions: Trilaciclib prior to chemotherapy in patients with ES-SCLC reduced incidence of CIM and need for supportive care in CIM across all treatment settings. Micro Abstract: Area and reason for the study: Extensive-stage small-cell lung cancer (ES-SCLC). To analyze the effect of trilaciclib on Chinese and Caucasian patients. Approach taken, including aspects such as the sample size: This pooled analysis included one study in China and three studies in western countries, and the overall sample size was 325. Overall result: Trilaciclib provides protection from CIM. General significance of the findings: The consistent efficacy of trilaciclib can be observed from pooled data across different treatment lines. All information should be accessible to a nonexpert audience.